Susceptibility to Hyperglycemia in Rats With Stress-Induced Depressive-Like Behavior: Involvement of IL-6 Mediated Glucose Homeostasis Signaling - Li, Xiaojuan; Qiu, Wenqi; Li, Nan; Da, Xiaoli; Ma, Qingyu; Hou, Yajing; Wang, Tingye; Song, Ming; Chen, Jiaxu (Frontiers in Psychiatry, 2020)
Depression is a common psychiatric disorder comorbid with diabetes and may lead to high morbidity, disability, and mortality. However, the underlying mechanism behind their association remains unknown. Cytokine-mediated inflammation in brain may play important roles in the pathogenesis of depression and insulin resistance. In the present study, we subjected the rats to chronic unpredictable mild stress (CUMS) for 3 to 8 weeks. The tests to ascertain depression-like behaviors including open field test (OFT) and forced swimming test (FST) were performed, and levels of morning fasting blood glucose, triglyceride (TG), total cholesterol (CHOL), high density lipoprotein cholesterol (HDL-C), and low density lipoprotein cholesterol (LDL-C), body weight, food intake, histopathological examinations of liver, adipose tissues and hypothalamus, hypothalamic GLUT4 as well as the IL-6-mediated glucose homeostasis signaling pathway were measured. The results showed that CUMS exposure resulted in the depression-like behavior at various time points in rats. Moreover, the rats exhibited increased peripheral glucose levels, impaired hepatocytes and hippocampal neurons, and decreased hypothalamic GLUT4 levels after 6 weeks of CUMS exposure. Meanwhile, activated IL-6 but suppressed IL-6-mediated glucose homeostasis signaling was observed in the hypothalamus. Markers of lipid metabolism including TG, CHOL, HDL-C and LDL-C were dysregulated, and body weight and food intake were decreased in the CUMS-exposed rats. Our results show that depressed rats induced by 6-week CUMS stimulation display susceptibility to hyperglycemia, which is associated with IL-6-mediated inhibition of glucose homeostasis signaling in the hypothalamus.